Cortical bone thickness, base osteophyte occurrence and radiological signs of osteoarthritis in the fingers of male elite sport climbers: A cross-sectional 10-year follow-up study - Pastor, T.; Fröhlich, S.; Pastor, T.; Spörri, J.; Schweizer, A. (Frontiers in Physiology, 2022)
Background: Sport climbing places high mechanical loads on fingers. In 2012, our research group demonstrated adaptations of climbers` cortical bones with the presence of osteophytes compared to non-climbing controls.